Studi Meta-Analisis: Emotion Regulation Training Efektif Menurunkan Tingkat Kecemasan dan Depresi - Tiffani Narulita; Ananta Yudiarso (Humanitas (Jurnal Psikologi), 2023)
Anxiety disorders are emotions that are characterized by feelings of tension, worries, and increasing blood pressure that repeats continuously so that sufferers may avoid certain situations. Symptoms experienced by individuals with anxiety disorders often overlap with those of individuals with depression. Meta-analysis method was used to see the effectiveness of Emotion Regulation Training to reduce anxiety and depression levels. Results from 11 journals showed that the training was effective in reducing levels of anxiety and depression. The effect size score is -1.38 (95% CI -1.837 - -0.925, p value = <0.05) with I2 (inconsistency) 90.95%. These results indicate that Emotion Regulation Training is effective for reducing anxiety and depression levels.